Spontaneous hemothorax: A rare lethal pulmonary complication of neurofibromatosis type 1 (Indian Journal of Case Reports, 2021)
Neurofibromatosis 1 (NF1), also called von Recklinghausen’s disease, is an autosomal dominant disease characterized by multiple non-cancerous tumors of nerves and skin, and areas of abnormal pigmentation. Vasculopathy and spontaneous hemothorax are rare complications, but potentially lethal, which necessitates quick and decisive intervention to save the life of the patient. Here, we present a case of spontaneous massive haemothorax leading to hemorrhagic shock in a 66-year-old woman with neurofibromatosis type-1. She was investigated and managed successfully.